2019
DOI: 10.9734/ijpss/2019/v28i230102
|View full text |Cite
|
Sign up to set email alerts
|

Salt Resistance of Tomato (Lycopersicon esculentum Mill.) Cultivars Produced in Benin at Germination Stage

Abstract: Aims: In this research study, salt resistance level of seven tomato cultivars grown in Benin, namely Akikon, Tounvi; F1 Mongal, Petomech, Padma, TLCV 15 and Thorgal was evaluated at the germination stage. Study Design: The experiment was laid out as a completely randomized design with four replications. Place and Duration of Study: The experiment was carried out in the Laboratory of Plant Physiology and Abiotic Stresses Study of University of Abomey-Calavi, Republic of Benin from May to June, 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Crop production in saline areas largely depends upon successful germination, seedling emergence and establishment and efficient reproductive phase (Bartels and Sunkar, 2005). Although most and eventually all cultivated plants are glycophyte species, their overall responses to increasing NaCl dose appear to be species-specific (Wouyou et al, 2016 and2017;Kpinkoun et al, 2018 andKinsou et al, 2019). Moreover, within a given species, a substantial variation in salt sensitivity may occur among cultivars (Ould Mohandi et al, 2011;Manaa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Crop production in saline areas largely depends upon successful germination, seedling emergence and establishment and efficient reproductive phase (Bartels and Sunkar, 2005). Although most and eventually all cultivated plants are glycophyte species, their overall responses to increasing NaCl dose appear to be species-specific (Wouyou et al, 2016 and2017;Kpinkoun et al, 2018 andKinsou et al, 2019). Moreover, within a given species, a substantial variation in salt sensitivity may occur among cultivars (Ould Mohandi et al, 2011;Manaa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Así mismos, la apariencia de las plántulas coincide con lo descrito por Kinsou et al (2019) y Baruah et al (2019) quienes mencionan que algunos síntomas por exceso de metales son: desarrollo limitado o deformación de radícula, quemaduras de testas y/o radículas SUSTAINABLE AGRICULTURE (visualmente identificado por oscurecimiento o coloración intensa) y supresión del desarrollo del embrión reflejado en una disminución en el porcentaje de germinación o en la velocidad de esta.…”
Section: Evaluación Del Sustrato En Germinaciónunclassified
“…However, despite a substantial amount of literature on response of tomato to salinity stress, little information is available on salt resistance of tomato cultivars produced in Benin. In our previous study, we have demonstrated that there is a variability of relative salt-stress resistance among the same tomato cultivars at the germination stage (Kinsou et al, 2019). Since salt-resistance at the germination stage is not necessarily correlated with salinity resistance at subsequent developmental stages, the present study aims at evaluating NaCl stress effects on young plant growth of the same seven tomato cultivars grown in Benin.…”
Section: Introductionmentioning
confidence: 96%